The Water, Energy, and Food Nexus: Health is yet Another Resource - Nuwayhid, Iman; Mohtar, Rabi (Frontiers in Environmental Science, 2022)
This perspective highlights a place for Health (H) in the Water, Energy, and Water (WEF) nexus. It reviews the reference to health in the WEF nexus literature and makes the case for its inclusion into the WEF Nexus. We argue that although the nexus concept of water, energy, and food is relatively recent, it has been adopted by several UN agencies and international organizations and it will continue to draw emphasis in research, politics and communications of the scientific community. Now is the time to integrate health.